Description and evaluation of an ultra-processed food consumption score for children - Anna Müller; Caroline dos Santos Costa; Romina Buffarini; Juliana dos Santos Vaz; Marlos Rodrigues Domingues; Pedro Curi Hallal; Janaina Vieira dos Santos Motta (Revista de Saúde Pública)
ABSTRACT OBJECTIVE To present a screener for consumption of ultra-processed foods for children in early childhood, evaluating the ability of the score generated by this screener to reflect the participation of ultra-processed foods in children’s diets. METHODS This study was conducted with a convenience subsample of the 2015 Pelotas Birth Cohort (n = 365). The mothers of the participating children answered a food consumption questionnaire the day before the interview (screener) containing 16 subgroups of ultra-processed foods, followed by a traditional 24-hour food recall (24hR). Each participant’s ultra-processed food consumption score corresponded to the number of food subgroups consumed and the percentage of energy derived from the participation of ultra-processed foods in the diet on the same day was calculated from the answers in the 24hR. The association between the score and the percentage of energy from ultra-processed foods was tested using linear regression models. The degree of agreement between the classification of participants according to approximate fifths of the percentage of calories from ultra-processed foods and according to the score intervals was assessed using the Pabak index. RESULTS The average percentage share of ultra-processed foods in the total caloric value of the diet, calculated using the 24hR, was directly and significantly associated with an increase in the ultra-processed food consumption score. There was substantial agreement between the ranges of the ultra-processed food consumption score obtained by the screener and the approximate fifths of the share of ultra-processed foods in the diet calculated by the 24hR (Pabak index = 0.65). CONCLUSIONS The ultra-processed food consumption score, obtained from an ultra-processed food consumption screener, a practical and agile instrument, is capable of reflecting the participation of ultra-processed foods in children’s diets, with regard to the 2015 Pelotas Birth Cohort.